Aplicación de la justicia restaurativa en la determinación de la sanción penal juvenil en los juzgados de familia de Loreto en Iquitos, 2020-2023 - Hidalgo Paredes, Silvia (2025)
This research primarily aimed to analyze the relationship between the application of restorative justice and juvenile criminal sanctions. A descriptive documentary methodology was employed, based on a systematic review of specialized literature, official reports, and national and international precedents. Data was processed through thematic content analysis and the interpretation of statistical correlations from a hypothetical study (Table 03), specifically Kendall's Tau-b test. Key results indicated no statistically significant correlation was found between the application of restorative justice and juvenile criminal sanctions, leading to the acceptance of the null hypothesis. This suggests that, in the studied domain, the implementation of restorative processes did not directly translate into variations in the sanctions imposed on adolescent offenders. It was concluded that this lack of relationship might be due to the limited formal integration of restorative outcomes into sentencing decisions and potential institutional barriers. Recommendations include legislative review of the regulatory framework, training for justice operators on integrating restorative justice, and strengthening inter-institutional coordination. The study highlights the need for future mixed-methods and longitudinal research to better understand the factors mediating this relationship.